2006
DOI: 10.1002/cncr.21690
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin, ghrelin, and leptin in cancer cachexia in breast and colon cancer patients

Abstract: Objective To evaluate the efficacy and safety of the interleukin‐1 inhibitor rilonacept (interleukin‐1 Trap) for gout flare prevention during initiation of uric acid–lowering therapy (ULT). Methods In total, 241 adult patients with gout, ≥2 gout flares within the past year, and a serum urate level ≥7.5 mg/dl were initiated on allopurinol 300 mg daily and randomly allocated in a 1:1:1 ratio to receive 16 once‐weekly subcutaneous injections of placebo, rilonacept 80 mg, or rilonacept 160 mg, with a double (loadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
98
3
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(118 citation statements)
references
References 67 publications
6
98
3
7
Order By: Relevance
“…In animals, both higher (Hanada et al, 2004) and lower ghrelin levels than controls are reported. Several studies showed higher ghrelin levels (Shimizu et al, 2003;Garcia et al, 2005) or higher levels only in subgroups (61% of 18 breast and colorectal cancer patients) (Wolf et al, 2006) in patients with CACS as compared to non-cachetic cancer patients or healthy controls; however, normal (Huang et al, 2007) ghrelin levels were reported as well. The differences of fasting levels of ghrelin in cancer patients may be explained by differences in BMIs, 20.7 kg m À2 in LD and 20.6 kg m À2 in UD, and 18.5 kg m À2 in others (Shimizu et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In animals, both higher (Hanada et al, 2004) and lower ghrelin levels than controls are reported. Several studies showed higher ghrelin levels (Shimizu et al, 2003;Garcia et al, 2005) or higher levels only in subgroups (61% of 18 breast and colorectal cancer patients) (Wolf et al, 2006) in patients with CACS as compared to non-cachetic cancer patients or healthy controls; however, normal (Huang et al, 2007) ghrelin levels were reported as well. The differences of fasting levels of ghrelin in cancer patients may be explained by differences in BMIs, 20.7 kg m À2 in LD and 20.6 kg m À2 in UD, and 18.5 kg m À2 in others (Shimizu et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Morning fasting levels of ghrelin in patients (Shimizu et al, 2003;Garcia et al, 2005;Wolf et al, 2006;Huang et al, 2007) or animals (Hanada et al, 2004;Liu et al, 2006) with CACS are still poorly understood. In animals, both higher (Hanada et al, 2004) and lower ghrelin levels than controls are reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is produced primarily by the mammalian gastric enteroendocrine cells of the oxyntic mucosa, likely the X/A-like cells [6] . It has been reported that there was an increase in the levels of total ghrelin in cachectic lung [7] , breast and colon [8] cancer patients. Ghrelin infusion has recently been shown to increase appetite in subjects with cancer-induced cachexia [9] .…”
Section: Introductionmentioning
confidence: 99%